Multifaceted analyses reveal carbohydrate metabolism mainly affecting the quality of postharvest bamboo shoots - Li, Zhen; Xu, Xiurong; Yang, Kebin; Zhu, Chenglei; Liu, Yan; Gao, Zhimin (Frontiers in Plant Science, 2022)
Bamboo shoot is one of nutritious vegetables in China. However, the edible quality of fresh bamboo shoots deteriorates easily after harvest. Here, morphological, physiological, transcriptomic and microRNA sequencing analyses were conducted to investigate the postharvest characteristics of moso bamboo (Phyllostachys edulis) shoots. Rapid decreases of soluble sugars, structural polysaccharides and hydrolyzed tannins, and increases of lignin and condensed tannins were observed in the postharvest bamboo shoots. Differentially expressed genes and miRNAs with opposite trends were mainly enriched in structural polysaccharide metabolism, starch and sucrose metabolism and glycolysis pathways, which were consistent with the changes of carbohydrates. A co-expression network of carbohydrate metabolism was constructed, which was verified by qPCR and yeast one-hybrid (Y1H) assay. Furthermore, the function of one hub glycosyltransferase gene was validated in Arabidopsis, which confirmed that it was involved in xylan biosynthesis. These results are of great significance for revealing the carbohydrate metabolism mechanisms of postharvest bamboo shoots and provide a potential candidate gene for molecular breeding related to xylan in the future.